Expression of p16 in pterygium and its relation with epithelial dysplasia and possible etiologic role of HPV - Elçin Süren; Döndü Nergiz; Dinç Süren; Arsenal Sezgin Alikanoğlu; Hülya Tosun Yıldırım; Zelal Akgündüz Altun (Wolters Kluwer Medknow Publications, 2022)
Context: p16 is an important tumor suppressor gene and responsible for regulating the cell cycle. Diffuse positivity with p16 in the cervix and head/neck carcinomas can be regarded as a surrogate marker of the presence of high-risk human papillomavirus (HPV). Aim: The aim of our study was to search the existence of p16 expression in pterygium. We also analyzed the association of p16 expression with epithelial dysplasia and HPV expression. Subjects and Methods: The study enrolled 75 cases of pterygium. The conjunctival tissues of 10 patients excised by the strabismus surgery were used as control group. All of the slides were stained with p16 via the immunohistochemical method. Results: 49 (65%) of pterygiums showed low-grade epithelial dysplasia. None of the control groups showed dysplasia. Positive expression of p16 in patient group was significantly higher (P < 0.001). Staining percentage (SP) of p16 was between 0 and 26% in pterygium; mean SP was 5.1%. There was no staining in the control group. A total of 59 (72%) pterygium cases were positive with p16. Appoximately 42 of 49 (85%) cases with dysplasia showed p16 staining. There was a significant relation between dysplasia and positive expression of p16 (P < 0.001). Conclusions: P16 is significantly expressed in pterygium and correlated with epithelial dysplasia. Furthermore, the existence of p16 expression suggests that HPV is a possible ethiological factor in pterygium. We think that examination of p16 expression and analysis of HPV DNA in p16 positive cases can help us to understand the etiopathogenesis of the disease better.